Current research on bruchids in Uganda - Silim, M.N. (International Center for Tropical Agriculture, 1991)
Zabrotes subfasciatus and Acanthoscelides obtetus are widely distributed in Uganda. A. obtectus is the predominant species in the cooler zones, while Z. subfasciatus is predominant in warmer areas. The former species is more common in grain warehouses while the latter is more common in on-farm storage. Examining the four bean lines EMP 175, K 20, White Haricot, and RAZ 2 in storage trials, it was found that RAZ 2 was resistant to Zabrotes. The remaining lines were susceptible. RAZ 2 contains arcelin, a seed protein, which confers resistance to Zabrotes. Results on farmers' perceptions, practices, and control of bruchids remains to be studied. Research on the efficiency of solar heat disinfestation of bruchids has been initiated. (AS)